Promise me Dad : a year of hope, hardship, and purpose - Biden, Joseph R (New York : Flatiron Books, 2017)
The former vice-president of the United States chronicles the difficult final year of his son's battle with cancer, his efforts to balance his responsibilities to the country and his family, and the lessons he learned.
Keywords: Biden, Joseph R; Biden, Beau, -- 1969-2015.; Vice-Presidents -- United States -- Biography; Fathers and sons -- United States -- Biography; Cancer -- Patients -- United States -- Biography; Presidents -- United States -- Election -- 2016.; United States -- Politics and government -- 2009-2017.